MODELS AND APPROACHES TO CHANGE AND CHANGE MANAGEMENT IN MODERN ORGANISATIONS - Nwachuku, Azuka; Okereka, Onofere Princewill Princewill; Mukoro, Akpomuvire (LPPM Universitas Malikussaleh, 2023)
This study compares a few well-known change management models to help readers better understand change management. For this reason, this study examines the notion of change and the forces behind organisational change. The analysis demonstrates that, despite certain variations among the models discussed, they all share the division of the change the management system into successive phases and the recognition of the role that human resources play in the process. Additionally, implications and lessons for change management in the public sector were introduced. According to the study's conclusion, companies that struggled to manage change would see a decline in employee loyalty and output. Conversely, companies that successfully handled change would gain a competitive edge that guarantees long-term success. Organisations, particularly those in the public sector, must comprehend and implement change management models in the post-Covid-19 era if they are to improve their capacity for long-term success.